Genetic Variability and Character Association in Roselle (Hibiscus sabdariffa L.) Genotypes for Fibre Yield and its Attributes - Satyanarayana, N. Hari; Visalakshmi, V.; Mukherjee, S.; Priya, Bhanu; Sarkar, K. K. (International Journal of Economic Plants, 2017)
Genetic variability, correlation and path analysis were studied in a set of sixty diverse genotypes of roselle (Hibiscus sabdariffa L.) during Kharif, 2013 at Agricultural Research Station, Ragolu (ANGRAU), Srikakulam District, Andhra Pradesh for eleven important traits. Phenotypic as well as genotypic coefficients of variability were high for the important productivity characters like fibre yield plant-1, dry stick weight plant-1, green fresh weight plant-1 and green dry weight plant-1 (for PCV) and medium for other characters like plant height and bark thickness. High heritability coupled with high expected genetic advance was observed for fibre yield plant-1, dry stick weight plant-1, green fresh weight plant-1 and green dry weight plant-1. Fibre yield per plant was found to be significantly and positively correlated with plant height, base diameter, bark thickness, green fresh weight plant-1, green dry weight plant-1 and dry stick weight plant-1. Plant height, base diameter, green fresh weight plant-1, green dry weight plant-1 and dry stick weight plant-1 also exhibited significant positive inter correlation among themselves. Partitioning of correlation coefficients of various components upon fibre yield plant-1 into direct and indirect contributions revealed that green fresh weight plant-1 has maximum direct effect upon fibre yield plant-1 followed by plant height, bark thickness and dry stick weight plant-1.